2004
DOI: 10.1016/s0741-5214(03)00712-2
|View full text |Cite
|
Sign up to set email alerts
|

Primitive proatlantal intersegmental artery and carotid endarterectomy

Abstract: Anastomotic connections between the developing internal carotid and basilar arterial system exist in early fetal life. Rarely, these carotid-basilar anastomoses will persist into adult life unilaterally or, rarely, bilaterally. 1 A 78-year-old woman was admitted to the Vascular Surgery Division of Padua University (VSDPU). For 30 days, she had experienced focal (transischemic attacks with right-sided paresis-5 episodes) and nonfocal (syncope and multiple attacks of vertigo) cerebral symptoms. Digital subtracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 1 publication
2
16
0
Order By: Relevance
“…Although some vascular variations have been described coexisting with the persistent PA, until now, we had not found a case of fusiform aneurysm of the subclavian artery with a persistent PA. The association of multiple atherosclerotic stenoses, along with persistent PA and appearance of multiple calcified atherosclerotic plaques, is consistent with data found in the literature 5,8,12 . The extremely calcifications of both CCA that were present in our case have not been described in recent publications.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although some vascular variations have been described coexisting with the persistent PA, until now, we had not found a case of fusiform aneurysm of the subclavian artery with a persistent PA. The association of multiple atherosclerotic stenoses, along with persistent PA and appearance of multiple calcified atherosclerotic plaques, is consistent with data found in the literature 5,8,12 . The extremely calcifications of both CCA that were present in our case have not been described in recent publications.…”
Section: Discussionsupporting
confidence: 91%
“…The extremely calcifications of both CCA that were present in our case have not been described in recent publications. The unfortunate outcome of our patient, sadly confirmed that our early aggressive approach towards a surgical management, fearing that a persistent PA could be a source of further complications for the surgeon performing carotid endarterectomy, was right 8,12 . The absence of one or both VA provides an important clue in the diagnosis of persistent fetal vascular communication between carotid and vertebrobasilar arteries.…”
Section: Discussionsupporting
confidence: 58%
“…The use of a shunt was anatomically difficult. 10 Even if routine use of cerebral monitoring and a shunt is recommended, in our experience, high blood pressure is sufficient in most cases, especially when a complete circle of Willis coexists. 7,8,10 Some authors have reported ICA lesions with proatlantal intersegmental artery treated by an endovascular approach.…”
Section: Discussionmentioning
confidence: 69%
“…10 Even if routine use of cerebral monitoring and a shunt is recommended, in our experience, high blood pressure is sufficient in most cases, especially when a complete circle of Willis coexists. 7,8,10 Some authors have reported ICA lesions with proatlantal intersegmental artery treated by an endovascular approach. 11,12 We found that this was not a good indication due to the high embolic risk with these symptomatic lesions during the catheterism or the ICA stenting covering the ECA.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation